Malamih al-Ashwat al-'Arabiyyah wa Makharijaha - Kasim, Amrah Muhammad (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2015)
This writing discusses on al-ashwat al-â€˜arabiyyahÂ that is known with â€œphoneticâ€ term. It talks and interprets makharijÂ al-hurufÂ or place for producing sounds and also processing production of sounds by parts of mouth in Arabic language. The problems of sounds and its systems in Arabic language have been conducted by the scholars of al-ashwat al-â€˜arabiyyah attractively, neatly, and detailÂ and gotten ahead the phonetic western scholars. Part of their analysis results formulate the study aboutÂ al-ashwat al-sakinahÂ (al-Shamit) is known with vocal and consonant sounds in research questions shawaitÂ â€“Â shawamit. Ibnu Jinni has formulated â€œharakatâ€(wowel in Arabic language) and dimension of letter Â madÂ andÂ liynÂ on alifÂ  letter -Â wawÂ -Â yaâ€™ (Ø§ Ùˆ ÙŠ), from these letters create Â harakat fathah, dammah, and kasrah. Moreover, in this writing also exist the description of hijaâ€™i letters and its makhraj that are correct from parts of mouth and the unity of coordinative sounds that produce sounds in morphemes arrangement, in one word that produces meaning. The result of phonological study has divided al-ashwat to beÂ kinds of sound like the pronounced sounds, produced sounds from mouth, and heard sound.Â